Through a Vegan Studies Lens : Textual Ethics and Lived Activism - Wright, Laura, 1970- (Book collections on Project MUSE., 2019)
"The essays in Doing Vegan Studies are engaged with doing theory differently. This collection showcases established and emerging writers who are doing vegan theory, an international mix of activist scholars, affiliated with the academy and doing work beyond it - a distinction that marks vegan studies as a pedagogy and scholarly venue that is not exclusive and that owes its existence to lived animal rights activism"--Provided by publisher.